Comparison of shear bond strength of orthodontic attachments bonded to sandblasted amalgam with different adhesives - Forogh Khalilinejad; Shiva Alavi (Isfahan University of Medical Sciences, 2011)
Introduction: Bonding orthodontic attachments to large amalgam restorations of posterior teeth is a challenge. The aim of this study was to evaluate and compare the shear bond strength (SBS) of orthodontic attachments bonded to amalgam with different chemical surface preparations.Materials and methods: In this in vitro study 105 convex amalgam surface samples were subjected to aluminium oxide sandblasting. The amalgam sampless were randomly divided into three equal groups. In each group buccal tubes were bonded with Transbond Plus using Reliance Metal Primer (RMP), All Bond II (AB2), and Alloy Primer (AP). Thirty-five human teeth served as the controls to test buccal tube bonding to acid-etched enamel with Transbond Plus and Transbond XT. All the samples were stored in artificial saliva; after thermocycling for 1000 times, all the sampels were tested for SBS. Data were analysed with Kruskal-Wallis and Mann-Whitney tests.Results: There were statistically significant differences in SBS values between all the groups (p value < 0.001). AB2 created the strongest bond to amalgam (6.75 MPa). However, there were no significant differences between SBS values achieved with AB2 and those in the control group (p value = 0.455). No Significant differences were observed between AP and RMP (p value = 0.051) but both had significant differences with the control group (p value < 0.001).Conclusion: The results of the present study revealed that AB2 intermediate resin is useful for strong bonding of metal orthodontic attachments to dental amalgam.Key words: Acrylic resin, Artificial saliva, Dental amalgam, Shear bond strength.